Public health impact and cost-effectiveness of implementing a 'pre-vaccination screening' strategy with the dengue vaccine in Puerto Rico. Issue 50 (28th November 2022) - Thommes, Edward; Coudeville, Laurent; Muhammad, Riyadh; Martin, Maria; Nelson, Christopher B.; Chit, Ayman
Highlights: A tetravalent dengue vaccine has been licensed for use in several countries. A 'pre-vaccination screening' implementation strategy is the WHO and CDC recommended option. In Puerto Rico, this strategy would be cost effective from a payer perspective using WHO threshold criteria. In Puerto Rico, this strategy would be cost saving from a societal perspective. Abstract: Background: The World Health Organization (WHO) recommended 'pre-vaccination screening' as its preferred implementation strategy when using the licensed dengue vaccine (CYD-TDV; Dengvaxia, Sanofi), so that only individuals with previous dengue infection are vaccinated. The US Centers for Disease Control and Prevention (CDC) recommended use of CYD-TDV to prevent dengue in children with previous laboratory-confirmed dengue infection in regions where dengue is endemic. Here, we evaluate the public health impact and cost-effectiveness of a 'pre-vaccination screening' strategy in Puerto Rico. Methods: The current analysis builds upon a previously published transmission model used to assess the benefits/risks associated with dengue vaccination. For 'pre-vaccination screening', three alternative testing methods were assessed: one using an immunoglobulin G (IgG) enzyme-linked immunosorbent assay (ELISA) dengue serotest, another with dengue serotesting using a rapid diagnostic test (RDT), and one using both sequentially (as recommended in Puerto Rico). The time horizon considered was 10 years. Results: In Puerto Rico, the disability-adjusted life years (DALYs) averted for 'pre-vaccination screening' with an ELISA-based program, RDT-based program, and both sequentially would be a median 1, 192 (95% CI: 716–2, 232), 2, 812 (95% CI: 1, 579–5, 019), and 1, 017 (95% CI: 561–1, 738), respectively. These benefits would arise from the reduction in cases: median 24, 961 (95% CI: 17, 480–36, 782), 58, 273 (95% CI: 40, 729–84, 796), 20, 775 (95% CI: 14, 637–30, 374) fewer cases, respectively. The cost per DALY averted from a payer perspective would be US$12, 518 (95 %CI: US$4, 749–26, 922), US$10, 047 (95% CI: US$3, 350–23, 852), and US$12, 334 (95% CI: US$4, 965–26, 444), respectively. All three strategies would be cost saving from a societal perspective. Conclusions: Our study supports the WHO and CDC 'pre-vaccination screening' guidance for CYD-TDV implementation. In Puerto Rico, regardless of the testing strategy and even with a relatively low rate of testing, it would be cost-effective from a payer perspective and cost saving from a societal perspective.